Morphometry of the external auditory canal: Radiological study - Çalışkan, Selma; Çetin, Hüseyin; Akkaşoğlu, Sinem (Journal of Surgery and Medicine, 2020)
Aim: Morphometry of the external auditory canal was not previously studied among the normal population in the literature. In this study we aimed to indicate normal values and age, gender, and side related changes of the external auditory canal of healthy individuals. Methods: Computed Tomography (CT) images of 379 patients were evaluated in this cross-sectional study. Two diameters at three points were measured on sagittal images for each side: First point was at the level of the tympanic membrane where chorda tympani leaves the bony canal. The height (1a) and width (1b) were measured from the ground where the cylindrical view of EAC was most prominent. The second point was at isthmus level, where height (2a) and width (2b) were measured. The third point was the most lateral site of external auditory canal (EAC) at the level of the tympanomastoid suture where height (3a) and width (3b) were measured. Age, gender, and side related changes for each measurement were statistically analyzed. Results: The diameter of each point in each direction was similar between the left and right sides. The median diameter of left 1a was 9.4 mm in males and 9.2 mm in females, which was significantly different. The “a” diameter of each point was higher in males than females for both sides. There was no significant difference between males and females in terms of b diameters. Diameter 1b was higher on the left side compared to the right side for females, while left-right side comparisons for other measurements were similar. None of the diameters differed between the left and right sides for males. Conclusion: Normal measurements of EAC diameters and its age, sex and side related changes are important for surgeons, radiologists, and anatomists. Proper evaluation of EAC is critical for transcanal endoscopic ear surgery and early diagnosis of a pathology impairing the anatomy of EAC on radiologic images.